EU Accession : Norms and Incentives - Glencorse, Blair (World Bank, Washington, DC, 2017)
The European Union (EU) is one of the most successful examples in recent times of the peaceful regional expansion of prosperity and stability through institutional structures and shared resources. The EU has supported a process of governance and economic development across the European continent which now encompasses 27 member countries and over 500 million people. EU accession is a process of alignment through which acceptance of the acquis communautaire (the body of EU law) in aspiring states leads to the reorganization of an entire corpus of political, social, economic and cultural relationships, with the Commission and the Council explicitly negotiating, agreeing upon, refereeing and monitoring these linkages. These technical and political changes- largely generated through accession conditionality are accompanied by a process of 'Europeanization' by which all EU countries come to adopt European norms and values, transferred through many different routes including declaratory policies and documents, small-scale projects, and socialization between governments. In combination, the transformation that the concept and process of Europe has brought about is extraordinary- indeed in many ways it can be argued that the EU accession process has overcome the aid complex and its inefficient parallel systems and short-term projectized approaches which can often prevent exactly these successful outcomes in developing countries today. That is not to suggest, however, that the project of European enlargement is a single monolith, or has been equally successful in all EU accession countries. In certain contexts it has generated real and important reforms, while in others, positive institutional change has been far less clear. Moreover, problems with the process remain, and moving forward the EU will itself need to adapt to new realities and changing dynamics in order to ensure that future enlargement is as successful as past accession.